Infrastructure of Public-Scientific Partnership (PSP) in Spatial Development of the Russian Far-East and North-Eastern Asia - Boris Krasnopolski (European Regional Science Association (ERSA), 2014)
The Public-Scientific Partnership (PSP) is examined as a mechanism of the interests' coordination of the regional scientific organizations, government bodies and local businesses in realization of the detailed scientific researches of the social-economic and ecological development and introduction of their applied results into the practical economy. The Infrastructure of PSP is a network of the "technological chain" between all these organizations that is created in the concrete region or in the inter-regional/international system. This infrastructure has the inside and outside elements. The implementation of this project is based on the huge complex of the scientific researches described in the monograph "Pacific Russia ? 2050" (Synthesis of the applied results of the scientific-technical and economic prognosis / editors: P. Minakir, V. Sergienko), Vladivostok, 2011. First of all, the regional and inter-regional/international analysis of development of the inside and outside elements of the PSP infrastructure should be realized. It is reviewed all the necessary technological chains: "scientific organizations - government structures ? local businesses" on example of the Russian Far East by the most important economic branches. The estimation of the main international infrastructure elements of PSP is realized also for the North-Eastern Asia. The role of all these countries, including Russian Far-East, is discussed in formation of the inter-regional infrastructure network and the institutional state and regional bodies for practical realization on the infrastructure projects in this zone. These analysis and estimations are based on the Declarations of the Asia-Pacific Ministerial Conferences on Public-Private Partnerships (PPP) for Infrastructure Development in Jakarta and Tehran (2010 and 2012) including materials of a High-level Expert Group Meeting in Tehran (2012) organized by the United Nations Economic and Social Commission for Asia and the Pacific (ESCAP). The foreign experience of the organizational-methodical approaches in the use of the regional analysis and mechanisms of the infrastructure formation is discussed also in connections with the scientific researches in the area of the spatial economy.
Keywords: R11; 330; Public-Scientific Partnership (PSP); PSP Infrastructure; Russian Far East; North-Eastern Asia; Declarations of Ministerial Conferences for Infrastructure Development; R110